1992
DOI: 10.1007/bf00298453
|View full text |Cite
|
Sign up to set email alerts
|

Mature sacrococcygeal teratoma containing the lower half of a human body

Abstract: Twins were diagnosed by ultrasound in a 29-year-old woman. The cesarean delivery revealed at first a mature girl with a large benign sacrococcygeal teratoma and then a healthy boy. X-ray and CT examinations of the teratoma showed pelvic and lower limb bones. A mature teratoma-tridermoma (weight 475 g) containing the underdeveloped lower half of a human body was confirmed during surgery and verified morphologically. The fraternal twins, i.e., the girl operated upon and her brother, have been followed for 5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In six instances the intact skin of the autosite covered a pocket containing a typical fetiform structure, all with limbs (upper, lower, or both) whereas one consisted of the entire caudal half of a fetal body (Fig. 10) (Parizek et al, 1992); teratomatous tissue was found in at least two. In the seventh case, resulting from in vitro fertilization, a prenatal ultrasound examination showed a fetus with a sacrococcygeal mass surrounded by a fluid-filled sac from which a liter of fluid was aspirated (in utero).…”
Section: Pygopagusmentioning
confidence: 99%
“…In six instances the intact skin of the autosite covered a pocket containing a typical fetiform structure, all with limbs (upper, lower, or both) whereas one consisted of the entire caudal half of a fetal body (Fig. 10) (Parizek et al, 1992); teratomatous tissue was found in at least two. In the seventh case, resulting from in vitro fertilization, a prenatal ultrasound examination showed a fetus with a sacrococcygeal mass surrounded by a fluid-filled sac from which a liter of fluid was aspirated (in utero).…”
Section: Pygopagusmentioning
confidence: 99%
“…An ocular lens present as lentinoids (lens-like cells), as well as a completely formed eye, have been found within sacrococcygeal teratomas 1011 Parizek et al reported a mature teratoma containing the lower half of a human body in one of fraternal twins 13…”
Section: Typesmentioning
confidence: 99%
“…These reports detail accessory appendages associated with lipomyelomeningoceles or sacrococcygeal teratomas. 9,17,18…”
Section: Discussionmentioning
confidence: 99%